Electronic Comic Media to Improve Elementary School Students’ Reading Interest and Reading Skills - Ni Luh Putu Dian Astari; I Ketut Gading; Ni Ketut Desia Tristiantari (Mimbar Ilmu, 2026)
Reading interest and reading skills among elementary school students remain significant challenges in the learning process, particularly amid the rapid development of digital technology. One of the factors contributing to this issue is the limited availability of learning media that can attract students’ attention and support interactive literacy learning. This study aims to analyze the effectiveness of electronic comic-based learning media in enhancing students’ reading interest and reading skills in elementary schools. This study employed a research and development design using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects involved elementary school students divided into experimental and control groups. Data were collected through reading interest questionnaires and reading skill tests using instruments that were aligned with the research objectives. The data were analyzed using descriptive and inferential analysis techniques. The findings revealed that the use of electronic comic-based learning media significantly improved students’ reading interest and reading skills compared to conventional learning methods. These findings indicate that interactive digital learning media can create more engaging learning experiences, enhance students’ involvement in the learning process, and support literacy development in elementary schools. The implications of this study may serve as a foundation for developing innovative digital learning media that are relevant to students’ characteristics and learning needs in the digital era.